I can't steal from a coworker if I work from home: Conceptual and measurement-related issues associated with studying counterproductive work behavior in a telework setting. Issue 3 (26th May 2016) - Holland, Samantha J.; Simpson, Kaila M.; Dalal, Reeshad S.; Vega, Ronald P.
ABSTRACT: Teleworkers are an increasingly large proportion of the workforce. Despite the popularity of telework, organizations are concerned that telework offers employees more opportunity to engage in counterproductive work behavior (CWB). We argue that current CWB scales are inappropriate for the telework setting because this context affects the types of employee behavior that can (a) feasibly be enacted and (b) conceptually be considered as CWB. In this article, we develop a CWB scale suitable for the telework setting (i.e., the T-CWB scale) by addressing the errors of contamination (commission) and omission present in existing CWB scales vis-à-vis the telework setting. We end by outlining an agenda for future research on CWB in the telework setting.